Pengaruh Gross Profit Margin (GPM), Debt to Equity Ratio (DER), dan Ukuran Perusahaan Terhadap Pertumbuhan Laba pada Perusahaan Subsektor Farmasi yang Terdaftar di BEI - Adawiyah, Nur Ribiyatun Al; Huda, Nurul; Alwi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the effect of Gross Profit Margin (GPM), Debt to Equity Ratio (DER), and company size on profit growth in pharmaceutical subsector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The study uses a quantitative approach with an associative research type. The research data are secondary data obtained from the company's annual financial reports, with a sample of four companies selected using a purposive sampling technique. The data were analyzed using multiple linear regression supported by the classical assumption test, coefficient of determination test, t-test, and F-test. The results show that partially GPM, DER, and company size do not significantly influence profit growth. This finding indicates that the level of gross profit margin, capital structure, and the size of company assets are not able to explain changes in profit growth individually in pharmaceutical subsector companies during the study period. The results suggest that profit growth in pharmaceutical companies is likely more influenced by factors other than the variables studied, such as operational efficiency, market conditions, business strategy, and external factors that influence company performance.